Nitric acid chambering coconut shell carbon / ZSM-5 molecular sieve composite material and preparation method thereof
The composite of coconut shell charcoal and ZSM-5 molecular sieve was optimized by using nitric acid pore-expansion technology, which solved the problems of uneven pore structure and insufficient specific surface area, and improved the adsorption and catalytic properties of the composite material, making it suitable for environmental remediation and catalysis.
Patent Information
- Application Number
- CN202511586632.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-02
- Publication Date
- 2026-02-03
AI Technical Summary
The existing coconut shell carbon has an uneven pore structure and insufficient specific surface area. Furthermore, the performance improvement after combining ZSM-5 molecular sieve with coconut shell carbon is limited, resulting in the inability to fully utilize the adsorption and catalytic properties of the composite material.
The pore structure of coconut shell carbon was optimized by nitric acid pore-expanding technology and then combined with ZSM-5 molecular sieve. A reasonable nitric acid treatment and composite process was adopted, combined with wet cutting process, to prepare nitric acid pore-expanded coconut shell carbon/ZSM-5 molecular sieve composite material.
It significantly improves the pore structure and specific surface area of composite materials, enhances the adsorption capacity for macromolecular gases and organic pollutants, and exhibits excellent performance in catalytic reactions, making it suitable for environmental remediation, gas adsorption, and catalysis.
Smart Images

Figure CN121446444A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of preparation, modification of adsorbents and preparation and application of composite materials thereof, and particularly relates to a nitric acid reaming coconut shell carbon / ZSM-5 molecular sieve composite material and a preparation method thereof, which utilizes nitric acid to treat reamed coconut shell carbon and ZSM-5 molecular sieve to be compounded, so as to improve the adsorption and catalytic performance of the material. BACKGROUND
[0002] As a common biomass carbon material, coconut shell carbon has excellent physical and chemical properties, such as high specific surface area, rich pore structure and chemical stability, and is widely used in environmental protection, energy storage, catalysis, adsorption and other fields. However, in some specific applications, the pore structure of coconut shell carbon cannot meet the high performance requirements. In order to improve the performance of coconut shell carbon, common modification methods include acid treatment, heat treatment, gas reaming and the like. Among them, using strong acid (such as nitric acid) to acidize and treat the surface of carbon material can form more uniform and larger pores.
[0003] As a common acidizing agent, nitric acid not only can promote the oxidation reaction on the surface of carbon material, but also can introduce functional groups such as carboxyl and aldehyde groups on the surface of carbon, so as to enhance the hydrophilicity and adsorption capacity of coconut shell carbon, thereby improving its performance in water treatment, gas adsorption and the like. However, the influence of nitric acid concentration on the reaming effect is still an important research direction. Different concentrations of nitric acid may have different degrees of influence on the pore structure of carbon material during the treatment process. Too high concentration may cause excessive corrosion and damage the overall structure of the material; too low concentration may result in insignificant reaming effect.
[0004] As a catalytic material with regular cage-shaped pore structure, ZSM-5 molecular sieve is widely used in petroleum chemical industry, gas adsorption and catalytic reaction. In existing researches, most of them focus on the application of coconut shell carbon or ZSM-5 molecular sieve alone. In recent years, the composite of ZSM-5 molecular sieve and other materials (such as carbon material) has become an effective way to improve the catalytic performance. The composite of coconut shell carbon and ZSM-5 molecular sieve not only can take advantage of both, but also can further improve the adsorption and catalytic performance of the material. However, the research on the composite of the two is relatively less. In particular, how to optimize the composite method of coconut shell carbon and ZSM-5 molecular sieve through nitric acid reaming technology to obtain good pore structure and enhanced catalytic adsorption performance is still a technical problem to be solved.
[0005] Therefore, the present application proposes a nitric acid reaming coconut shell carbon / ZSM-5 molecular sieve composite material and a preparation method thereof, which realizes efficient composite of coconut shell carbon and ZSM-5 molecular sieve through reasonable nitric acid treatment and composite process, as well as wet cutting process, improves the pore structure and adsorption and catalytic performance of the composite material, and has wide application prospect. SUMMARY
[0006] (I) Technical problems to be solved In view of the certain limitations of existing coconut shell carbon in adsorption and catalytic performance, especially in the aspects of non-uniform pore structure and insufficient specific surface area, and the composite technology of ZSM-5 molecular sieve and coconut shell carbon has not been able to effectively improve the synergistic effect of the two, resulting in the performance of the composite material cannot be fully played, the present application proposes a kind of nitric acid reaming coconut shell carbon / ZSM-5 molecular sieve composite material and its preparation method, the pore structure of coconut shell carbon is optimized by nitric acid reaming technology, and is compounded with self-made ZSM-5 molecular sieve, to solve the technical problem of how to improve the adsorption and catalytic properties of the composite material.
[0007] (II) Technical solutions In order to solve the above technical problems, the present application proposes a preparation method of nitric acid reaming coconut shell carbon / ZSM-5 molecular sieve composite material, which comprises the following steps: S1. Carbonization treatment is carried out on the dried coconut shell to obtain coconut shell carbon; S2. The coconut shell carbon is activated under water vapor conditions, and after cooling to room temperature, it is ground into powder; S3. The powder coconut shell carbon is soaked in a nitric acid solution for reaming treatment, then washed with deionized water until neutral, and dried to obtain reamed coconut shell carbon powder; S4. Sodium hydroxide NaOH and tetrapropylammonium hydroxide TPAOH are added to deionized water, ultrasonic dissolution is carried out, then aluminum isopropoxide AIP is added to the solution, stirring is carried out until complete dissolution, and a synthesis raw material is obtained; S5. Tetraethyl orthosilicate TEOs is added dropwise to the synthesis raw material, stirring is carried out at room temperature, then phenyltriethoxysilane is added to the solution, stirring is continued, it is transferred to a hydrothermal reaction kettle, and hydrothermal reaction is carried out; S6. After the reaction kettle is cooled to room temperature, the lower layer powder is taken out to obtain ZSM-5 molecular sieve; the ZSM-5 molecular sieve is washed with deionized water until the washing liquid is neutral; the ZSM-5 molecular sieve is placed in a blast drying oven at 105 DEG C and dried overnight; the dried ZSM-5 molecular sieve is ground into powder, and the ZSM-5 molecular sieve powder is placed in a tube furnace at 550 DEG C and calcined for 8h; S7. The reamed coconut shell carbon powder and the ZSM-5 molecular sieve powder are placed in a beaker, excess deionized water is added, stirring is carried out using a disperser to make the powders uniformly mixed, after natural sedimentation, the bottom settled composite material is taken out; S8. The composite material is mixed uniformly with a binder, a strip-shaped binary composite material is obtained by extrusion, drying treatment is carried out, after cooling to room temperature, it is broken and sieved to obtain a nitric acid reaming coconut shell carbon / ZSM-5 molecular sieve composite material.
[0008] Further, in step S1, the dried coconut shell is carbonized at 500℃ for 60min to obtain coconut shell carbon.
[0009] Further, in step S2, the coconut shell carbon is activated by steam at 850℃ for 2h, and then ground into powder with a mesh size of 160-200 after being cooled to room temperature.
[0010] Further, in step S3, when the reaming treatment is performed, the powdered coconut shell carbon is soaked in a nitric acid solution with a concentration of 1M-5M overnight.
[0011] Further, in step S4, the molar ratio of SiO2, Al2O3, TPAOH, NaOH and H2O in the synthesis raw material is 25:1:5:2.5:1000, 50:1:10:5:2000 or 100:1:20:10:4000; wherein, the SiO2 is provided by TEOS and phenyltriethoxysilane, and the Al2O3 is provided by aluminum isopropoxide.
[0012] Further, in step S5, the mass ratio of SiO2 and phenyltriethoxysilane is 1:0.025; after adding tetraethyl orthosilicate TEOs, stirring is performed at room temperature for 1h; after adding phenyltriethoxysilane, stirring is performed at 70℃ for 2h; and the reaction is performed under hydrothermal conditions at 170℃ for 24h.
[0013] Further, in step S6, the ZSM-5 molecular sieve has a silica-alumina ratio of 50, and the particle is a powder with a mesh size of 260-300.
[0014] Further, in step S7, the mass ratio of the reamed coconut shell carbon powder and the ZSM-5 molecular sieve powder is 8:2.
[0015] Further, in step S8, the binder is carboxymethyl cellulose; the binder is foamed by using hot water according to a proportion of 5%wt of the composite material, injected into the composite material for sufficient stirring and mixing; the strip-shaped composite material is dried in a blast oven at 120℃ for 4h, and then broken and sieved to obtain a particle-shaped nitric acid reamed coconut shell carbon / ZSM-5 molecular sieve composite material with a mesh size of 10-20.
[0016] In addition, the application also provides a nitric acid reamed coconut shell carbon / ZSM-5 molecular sieve composite material prepared by the above method.
[0017] (Three) beneficial effects This invention proposes a nitric acid-modified pore-expanded coconut shell carbon / ZSM-5 molecular sieve composite material and its preparation method. By modifying the coconut shell carbon with nitric acid pore-expanding technology and combining it with ZSM-5 molecular sieve, the pore structure and specific surface area of the composite material are significantly improved, enhancing its adsorption capacity for macromolecular gases and organic pollutants. Furthermore, the composite material exhibits excellent performance in catalytic reactions, possessing higher reactivity and selectivity, and can be widely applied in environmental remediation, gas adsorption, and catalysis. This technology not only improves the overall performance of the material but also optimizes its preparation process, showing promising prospects for industrial applications. Attached Figure Description
[0018] Figure 1a This is an example of the pore size distribution of expanded-pore coconut shell AC under different nitric acid concentrations in an embodiment of the present invention. Figure 1b For BET specific surface area analysis. Detailed Implementation
[0019] To make the objectives, contents, and advantages of the present invention clearer, the specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples.
[0020] To investigate the optimal nitric acid concentration for pore expansion and the optimal silica-to-alumina ratio for ZSM-5 molecular sieves, samples were first prepared and screened. To investigate the effect of different nitric acid concentrations on the pore size of coconut shell charcoal powder, BET tests were performed on three types of coconut shell powder after pore expansion with nitric acid (as shown in Table 1). Figure 1a and 1b As shown, the specific surface area of the original coconut shell charcoal is 1370 m². 2 / g, with a mesoporous volume ratio of 14%. When the nitric acid concentration is 1M, the specific surface area reaches 1375m². 2 The concentration of activated carbon was similar to that of raw coconut shell activated carbon, but the mesopore volume ratio of the coconut shell activated carbon reached 18.4%, a significant increase compared to the raw coconut shell activated carbon. This indicates that low-concentration nitric acid treatment can effectively widen micropores and form mesopore channels, but the degree of pore widening is limited. When the nitric acid concentration increased to 3M, the specific surface area of the coconut shell activated carbon reached 1550 m². 2 While maintaining a pore size of / g, the mesoporous volume ratio increased to 26.9%, and the pore size distribution curve showed a distinct peak in the 2-6nm range, forming a mesoporous network conducive to rapid diffusion of gas molecules. However, when the nitric acid concentration increased to 5M, the specific surface area of the coconut shell charcoal decreased sharply to 1504.4m². 2 / g, and the micropore volume is 0.36cm³. 3 / g compared to 3M, the micropore volume is 0.42cm³. 3 The 8.3% reduction in nitric acid concentration is likely due to the collapse of the carbon framework and the destruction of the microporous structure caused by excessive oxidation of nitric acid. Considering the synergistic effect of specific surface area, pore volume, and pore size distribution, the concentration of nitric acid 3M exhibits the optimal mesoporous-microporous hierarchical structure characteristics.
[0021] Table 1 BET test results of coconut shell charcoal powder after reaming
[0022] The BET characterization test results of ZSM-5 molecular sieves with different silicon-aluminum ratios show that the silicon-aluminum ratio has a significant effect on the specific surface area and total volume of the molecular sieve. When the silicon-aluminum ratio is 25, the specific surface area of the ZSM-5 molecular sieve is 252.2 m 2 / g, and the total volume is 0.125 cm 3 / g. When the silicon-aluminum ratio increases to 50, the specific surface area significantly increases to 367.4 m 2 / g, and the total volume also increases to 0.183 cm 3 / g, showing the best pore structure. When the silicon-aluminum ratio increases to 100, the specific surface area slightly decreases to 365.8 m 2 / g, and the total volume also slightly decreases to 0.174 cm 3 / g. In summary, when the silicon-aluminum ratio is 50, the ZSM-5 molecular sieve exhibits the best BET characterization results, and the silicon-aluminum ratio of 50 is selected as the composite carrier substrate for subsequent experiments.
[0023] Table 2 BET characterization test results of ZSM-5 molecular sieves with different silicon-aluminum ratios
[0024] Example 1 S1. Carbonize 100 g of dried coconut shell at 500°C to obtain a carbonized product; S2. Activate the carbonized product with steam at 850°C for 2 h, and after cooling to room temperature, grind the coconut shell charcoal into a powder with a particle size of 160-200 mesh.
[0025] S3. Soak the coconut shell charcoal powder in a 1M nitric acid solution overnight, then wash it with deionized water until it is neutral, and dry it.
[0026] S4. Weigh 20 g of sodium hydroxide (NaOH), 508 g of tetrapropylammonium hydroxide (TPAOH), and add them to 3600 ml of deionized water, and ultrasonic for 10 min. Then add 40.8 g of aluminum isopropoxide (AIP) to the solution, and stir until completely dissolved.
[0027] S5. Add 1041.7 g of tetraethyl orthosilicate (TEOs) dropwise, then stir at room temperature for 1 h, and then add 30 g of phenyltriethoxysilane to the solution. Then continue to stir at 70°C for 2 h, and transfer to a hydrothermal reaction kettle, and react under hydrothermal conditions at 170°C for 24 h.
[0028] S6. After the reactor was cooled to room temperature, the lower layer of powder was removed. The molecular sieve was washed with deionized water until the wash liquid was neutral. The treated molecular sieve was placed in a forced air oven at 105°C and dried overnight. The dried molecular sieve was ground to a powder. The molecular sieve powder was placed in a tube furnace at 550°C for 8h to remove the template.
[0029] S7. 80g of coconut shell charcoal powder and 20g of ZSM-5 molecular sieve powder were placed in a beaker and an excess of deionized water was added. The mixture was stirred using a cutter until the powders were evenly mixed. After natural sedimentation, the bottom sedimented composite material was removed.
[0030] S8. After 10g of carboxymethyl cellulose was foamed using 50ml of hot water, it was injected into the composite material and stirred thoroughly. The mixture was evenly mixed. A strip-shaped binary composite material was obtained by extrusion. The material was dried in a forced air oven at 120°C for 4h. After natural cooling to room temperature, it was broken and sieved to 10-20 mesh to obtain a granular composite material. Example 2
[0031] The difference from Example 1 is that: S3. The coconut shell charcoal powder was soaked in 3M nitric acid solution overnight, then washed with deionized water until neutral, and dried. Example 3
[0032] The difference from Example 1 is that: S3. The coconut shell charcoal powder was soaked in 5M nitric acid solution overnight, then washed with deionized water until neutral, and dried.
[0033] Comparative Example The difference from Example 1 is that: S3. The coconut shell charcoal was not treated with nitric acid to enlarge the hole for comparison.
[0034] The mass ratio of coconut shell carbon in the composite material is 80%, so it is required to have high specific surface area, wear resistance, iodine adsorption value, carbon tetrachloride value, water capacity, etc. The physical properties of the series of composite products prepared in Examples 1-3 and Comparative Example are shown in Table 3. The performance indicators of the coconut shell carbon / ZSM-5 composite material (Examples 1-3) after nitric acid reaming are all better than Example 4. In terms of bulk weight and strength, Example 1 (403; 95.6) is relatively high, indicating that the material density is larger, but the other physical properties are poorer. The iodine value is a key indicator of the unsaturation of the material, and the iodine value of Example 2 is 1165, indicating that it has good chemical activity and reaction potential. The carbon tetrachloride adsorption value (CTC) directly reflects the adsorption capacity of the material, and Example 2 is 72.3, which is significantly better than other examples, showing good adsorption performance. Water capacity is an important indicator of the water-holding capacity of the material, and the water capacity of Example 2 is 87, which is higher than other examples, indicating that it has good hydrophilicity and water retention performance. Considering all the indicators, the BET specific surface area of Example 2 is the highest, reaching 1268.5 m 2 / g, and it also has excellent performance in iodine value and water capacity, showing good chemical activity and adsorption performance, and the bulk weight and strength are also balanced.
[0035] Table 3 Physical performance test results of each composite sample
[0036] In summary, Example 2 performs best and has higher advantages in various performance indicators, especially the balance and excellence in specific surface area, iodine value, CTC and water capacity, making it more competitive in practical applications.
[0037] The above is only the preferred embodiment of the present application, it should be noted that for those skilled in the art, without departing from the technical principles of the present application, a number of improvements and modifications can be made, these improvements and modifications should also be considered as the protection scope of the present application.
Claims
1. A method for preparing a nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve composite material, characterized in that, The preparation method includes the following steps: S1. Carbonize the dried coconut shells to obtain coconut shell charcoal; S2. Activate the coconut shell charcoal under steam conditions, cool it to room temperature, and then grind it into powdered coconut shell charcoal; S3. Powdered coconut shell charcoal is soaked in nitric acid solution for pore expansion treatment, then washed with deionized water until neutral, and dried to obtain pore-expanded coconut shell charcoal powder. S4. Add sodium hydroxide (NaOH) and tetrapropylammonium hydroxide (TPAOH) to deionized water, sonicate to dissolve, then add aluminum isopropoxide (AIP) to the solution and stir until completely dissolved to obtain the synthetic raw material; S5. Add tetraethyl orthosilicate (TEOs) dropwise to the raw materials, stir at room temperature, then add phenyltriethoxysilane to the solution, continue stirring, transfer to a hydrothermal reactor, and carry out the hydrothermal reaction. S6. After the reactor is cooled to room temperature, the lower layer of powder is removed to obtain ZSM-5 molecular sieve; the ZSM-5 molecular sieve is washed with deionized water until the washing solution is neutral; the ZSM-5 molecular sieve is placed in a forced-air drying oven at 105℃ and dried overnight; the dried ZSM-5 molecular sieve is ground into powder and the ZSM-5 molecular sieve powder is placed in a tube furnace at 550℃ and calcined for 8 hours; S7. Place the expanded-pore coconut shell carbon powder and ZSM-5 molecular sieve powder in a beaker, add excess deionized water, stir with a disperser to make the powder mix evenly, and after natural sedimentation, take the composite material that has settled at the bottom. S8. The composite material and binder are mixed evenly, and strip-shaped binary composite material is obtained by extrusion. After drying, it is cooled to room temperature, crushed and sieved to obtain nitric acid expanded pore coconut shell carbon / ZSM-5 molecular sieve composite material.
2. The method for preparing the nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve composite material as described in claim 1, characterized in that, In step S1, the dried coconut shells are carbonized at 500℃ for 60 minutes to obtain coconut shell charcoal.
3. The method for preparing the nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve composite material as described in claim 1, characterized in that, In step S2, the coconut shell charcoal is activated with steam at 850°C for 2 hours, then cooled to room temperature and ground into 160-200 mesh powder.
4. The method for preparing the nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve composite material as described in claim 1, characterized in that, In step S3, during the pore-expanding process, the powdered coconut shell charcoal is soaked overnight in a 1M~5M nitric acid solution.
5. The method for preparing the nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve composite material as described in claim 1, characterized in that, In step S4, the molar ratio of SiO2, Al2O3, TPAOH, NaOH and H2O in the synthesis raw materials is 25:1:5:2.5:1000, 50:1:10:5:2000 or 100:1:20:10:4000; wherein, SiO2 is provided by TEOS and phenyltriethoxysilane, and Al2O3 is provided by aluminum isopropoxide.
6. The method for preparing the nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve composite material as described in claim 1, characterized in that, In step S5, the mass ratio of SiO2 to phenyltriethoxysilane is 1:0.025; after adding tetraethyl orthosilicate (TEOs), the mixture is stirred at room temperature for 1 hour; after adding phenyltriethoxysilane, the mixture is stirred at 70°C for 2 hours; and the reaction is carried out under hydrothermal conditions at 170°C for 24 hours.
7. The method for preparing the nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve composite material as described in claim 1, characterized in that, In step S6, ZSM-5 molecular sieve is used to obtain powder with a silicon-to-aluminum ratio of 50 and a particle size of 260-300 mesh.
8. The method for preparing the nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve composite material as described in claim 1, characterized in that, In step S7, the mass ratio of expanded-pore coconut shell carbon powder to ZSM-5 molecular sieve powder is 8:
2.
9. The method for preparing the nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve composite material as described in claim 1, characterized in that, In step S8, the binder is carboxymethyl cellulose; the binder is foamed with hot water at a ratio of 5%wt of the composite material, injected into the composite material and stirred thoroughly to ensure uniform mixing; the strip composite material is dried in a forced-air oven at 120℃ for 4 hours, naturally cooled to room temperature, crushed and sieved to 10~20 mesh to obtain granular nitric acid expanded pore coconut shell carbon / ZSM-5 molecular sieve composite material.
10. A composite material of nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve, characterized in that, The nitric acid-enlarged pore coconut shell carbon / ZSM-5 molecular sieve composite material was prepared by the method described in any one of claims 1 to 9.
